Pembelajaran berasaskan web menggunakan geogebra bagi tajuk graf fungsi tingkatan 5 - Zainul Abidin, Nurul Izzah (2010)
In the present educational scenario, computers are part of a classroom’s facilities. The main application of the computers is to help learning and teaching processes. Web based learning is viewed as an effective means of delivering courses in the process of teaching and learning as this medium can support student-centered learning. Therefore, the purpose of this project is to develop the Web Based Learning using GeoGebra software to help the Form 5 student learning the topic of Graph of Function topic. The instructional design model is based on ADDIE while the contents are based on discovery learning theory and KBSM learning outcomes. The development of learning module is based on constructivism theory and using inductive approach in order to create interesting learning environment. Hopefully, with the development the learning module, it will enhance the efforts in using computer in school especially in smart schools and also help students to better understanding and gain proficiency in mathematics.